Relating Depth and Diversity of Bivalvia and Gastropoda in Two Contrasting Sub-Arctic Marine Regions - Egilsdottir, Hronn; McGinty, Niall; Gudmundsson, Gudmundur (Frontiers in Marine Science, 2019)
The need to understand species distribution- and biodiversity patterns in high-latitude marine regions is immediate as these marine environments are undergoing rapid environmental changes, including ocean warming and ocean acidification. By the year 2100, the seas north of the Greenland-Iceland-Faroe (GIF) topographic ridge are predicted to become largely corrosive to aragonite, a form of calcium carbonate commonly formed by calcifying molluscs. We examine depth-diversity relationships in bivalves and gastropods north and south of the GIF ridge, between 200 and 2000 m depth. We also identify bivalve and gastropod species that could be monitored to identify early signs of changes in benthic communities north of the GIF ridge, due to ocean acidification. Patterns of α-diversity were estimated through rarefaction, as E(S20). Regional and depth related β-diversity was analyzed and the additive contribution of species replacement (turnover) and species loss/gain (nestedness) to β-diversity calculated. Despite sharing a significant number of species, diversity patterns differed between the study regions. The diversity patterns also differed between bivalves and gastropods. North of the GIF ridge, the relationship between α-diversity and depth was unimodal with a predominant decrease in bivalve and gastropod α-diversity between 300 and 2000 m depth. Species assemblages in the deep bathyal zone were partly nested subsets of the assemblages in the shallow bathyal zone. South of the GIF ridge, patterns in α-diversity were more ambiguous. Alpha diversity decreased between 300 and 2000 m depth in bivalves, with no clear trend observed in gastropods. This finding contradicts the recognized increase in α-diversity in the bathyal zone in the North Atlantic basin, perhaps due to the oceanographic conditions directly south of the GIF ridge. In contrast to that observed north of the GIF ridge, nestedness did not contribute significantly to β-diversity south of the GIF ridge. This comparative study sheds new light on deep-sea diversity patterns of molluscs in the high-latitude North Atlantic and provides baseline data on species occurrences. This information can inform future assessment of the impact of environmental changes in these regions and management efforts.